Francis Webb Seeley correspondence - Seeley, Francis Webb.
Two ALsS (1871 September 19 and undated) written by Seeley to John Watts De Peyster regarding the battle of Fredericksburg, Va., during the Civil War.
Bookseller and army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: De Peyster, J. Watts -- 1821-1907 -- Correspondence; Fredericksburg, Battle of, Fredericksburg, Va., 1862.; United States -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- History -- Civil War, 1861-1865.; Army officers; Booksellers